Partisipasi Masyarakat Dalam Pembangunan Desa (Studi Kasus: Desa Babelan Kota, Kecamatan Babelan, Kabupaten Bekasi) - Uly, Miranda Nursinta; Rifai, Maulana; Febriantin, Kariena (Peneliti.net, 2024)
This study examines community participation in Babelan Kota Village Development. The problem that the researcher wants to examine is how the role of the community and community involvement in village development to find out the extent of cooperation between the government and the community in an effort to advance their region. This research uses qualitative research methods where the research conducted is descriptive. The results of this research were obtained directly from the field with adjusted theory according to Mulyadi (2009: 26-49), namely: from various aspects of planning, implementation, utilization, evaluation/supervision. From the results of research that the people of Babelan City Village participated in village development but not all people actively participated in providing ideas or suggestions, there was a miscommunication. The inhibiting factor is not only from the participation of the community but also from natural factors in Babelan Kota Village that are not supportive.